Nutrition in peri-operative esophageal cancer management. (3rd July 2017) - Steenhagen, Elles; van Vulpen, Jonna K.; van Hillegersberg, Richard; May, Anne M.; Siersema, Peter D.
ABSTRACT: Introduction : Nutritional status and dietary intake are increasingly recognized as essential areas in esophageal cancer management. Nutritional management of esophageal cancer is a continuously evolving field and comprises an interesting area for scientific research. Areas covered : This review encompasses the current literature on nutrition in the pre-operative, peri-operative, and post-operative phases of esophageal cancer. Both established interventions and potential novel targets for nutritional management are discussed. Expert commentary : To ensure an optimal pre-operative status and to reduce peri-operative complications, it is key to assess nutritional status in all pre-operative esophageal cancer patients and to apply nutritional interventions accordingly. Since esophagectomy results in a permanent anatomical change, a special focus on nutritional strategies is needed in the post-operative phase, including early initiation of enteral feeding, nutritional interventions for post-operative complications, and attention to long-term nutritional intake and status. Nutritional aspects of pre-optimization and peri-operative management should be incorporated in novel Enhanced Recovery After Surgery programs for esophageal cancer.